"She didn't want to…and I'd obviously insist": Canadian University Men's Normalization of their Sexual Violence Against Intimate Partners. Issue 1 (2nd January 2019) - Jeffrey, Nicole K.; Barata, Paula C.
ABSTRACT: Men's sexual violence against women is pervasive and is especially common in heterosexual intimate relationships. Little research has examined sexual violence in this relational context and from men's perspectives, including how they talk about and frame their behavior. The current research examined how men's sexual violence and accounts thereof reflected and enacted the normalization of violent heterosexuality. We used online surveys with 447 Canadian university men to screen for men who had used sexual violence in their most recent past or present relationship with a woman. Of these men, 71 (15.88%) reported at least one experience using sexual violence and 10 of these men participated in an in-depth interview to elaborate on their experiences. We used a feminist poststructuralist form of discourse analysis to analyze the interview transcripts. Results suggested that men often used language that helped them to position themselves and their sexual violence as normal and expected. However, they also often used alternative discourses and accounts about sexual violence, heterosexuality, and consent. We briefly discuss the implications of our results for educational campaigns and interventions.